Observations on Food Consumption Behaviors During the COVID-19 Pandemic in Oman - Ben Hassen, Tarek; El Bilali, Hamid; Allahyari, Mohammad S.; Al Samman, Hazem; Marzban, Soroush (Frontiers in Public Health, 2022)
Several countries across the globe took severe steps to break the spread of COVID-19 immediately following announcing the first cases. Numerous voices highlighted the disorderly food-related impacts of such containment measures, but there is a lack of first-hand, primary data. Accordingly, this paper aims to study the perceptions of the impacts of the COVID-19 pandemic on behaviors related to diet and food shopping on a sample of 356 adult in Oman. The research is based on an online survey delivered in Arabic via the Survey Monkey platform from Sept. 15 to Oct. 10, 2020. The questionnaire had 25 questions (multiple options and one option), subdivided into three parts. The study used the snowball sampling approach, and respondents were asked to distribute the survey in their networks. Descriptive statistics and various statistical tests (e.g. U-Mann Whitney, Kruskal-Wallis, chi-square) have been used to evaluate the study results. The study showed a significant shift in the attitude and behavior of respondents regarding food and health. Indeed, the paper findings indicated (i) a shift to healthier diets; (ii) a growth in the consumption of local products due to food safety fears; (iii) a shift in grocery shopping behaviors (with an increase in online shopping); (iv) the absence of food stockpiling in Oman; and (v) a reduction of food waste. Surprisingly, COVID-19 appears to bring many beneficial adjustments in Oman to make food consumption more sustainable and healthier.